Perceived Usefulness Influence on Digital Technology Use Intention: The Moderating Role of Resistance to Change - Kristioni, Revi; Agustinus Purna Irawan; Indra Widjaja (Journal of Science and Education (JSE), 2026)
This study examines how Perceived Usefulness (PU) influences Intention to Use (IU) digital technology, with Resistance to Change (RC) as a moderating variable, among employees of ABC Project. Grounded in the Technology Acceptance Model (TAM) and organizational change theory, the study tests whether dispositional resistance weakens the cognitive pathway from perceived usefulness to adoption intention. A cross-sectional survey was administered to 120 employees involved in the organization’s digital transformation initiative. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results indicate that PU has a strong positive effect on IU (β = 0.634, p < 0.001), while RC exerts a significant negative effect (β = −0.182, p = 0.009). The moderating effect of RC on the PU–IU relationship was not statistically significant (β = −0.006, p = 0.812), suggesting that cognitive value assessment and resistance operate through independent psychological mechanisms. The study contributes to TAM literature by empirically testing resistance as a boundary condition in a project-based organizational context and offers practical implications for change management in digital transformation initiatives.